Promising strategies and new opportunities for high barrier polymer packaging films - Huang, Hua-Dong; Ren, Peng-Gang; Zhong, Gan-Ji; Olah, Andrew; Li, Zhong-Ming; Baer, Eric; Zhu, Lei (Progress in polymer science, 2023)
The past decades have witnessed the rapidly growing interest in polymer films as the most commonly used packaging material due to their lightweight, versatility, low cost, and ease of manufacturing. However, there is a noticeable mismatch between the demanding requirements of various oxygen- or humidity-sensitive commodities and the poor barrier properties of single-component polymer films, thus giving rise to food spoilage, drug failure, as well as corrosion damage of electronic devices. In this review, we provide an in-depth introduction on the most promising strategies for developing high barrier polymer packaging films, including surface coating, polymer blending, and polymer nanocomposites. Specifically, the types of surface coatings, the dispersed phase morphology in polymer blends, the main factors for polymer nanocomposites containing large-aspect-ratio nanoplatelets, their dispersion morphology, the interfacial structure, and the crystalline structure of the matrix polymers can be tailored to maximize the gas barrier performance. Also, current challenges and perspectives for future development of high barrier polymer packaging materials are proposed. The new insight into the relationship between polymer processing, microscopic architecture, and barrier properties of polymer materials are expected to provide a valuable guide for developing high-barrier polymer packaging materials. [Display omitted]